Feasibility Studies on Underwater Laser Surface Hardening Process - Biao Jin; Min Li; TaeWoo Hwang; YoungHoon Moon (Advances in Materials Science and Engineering)
Laser surface hardening process is a very promising hardening method for ferrous and nonferrous alloys where transformations occur during cooling after laser melting in the solid state. This study experimentally characterizes laser surface hardening of tool steel in both water and air. For the underwater operation, laser surface scanning is performed over the tool steel surface which is immersed in water. The laser surface hardening tests are performed with a maximum 200 W fiber laser with a Gaussian distribution of energy in the beam. For the surface hardening, single-track melting experiment which sequentially scans elongated path of single line has been performed. As the hardened depth depends on the thermal conductivity of the material, the surface temperature and the penetration depth may be varied by underwater laser processing. The feasibility of underwater laser surface hardening process is discussed on the basis of average hardness level and hardened bead shape.